The natural function of the malaria parasite’s chloroquine resistance transporter - Sarah H. Shafik (Nature Portfolio, 2020)
Plasmodium falciparum chloroquine resistance transporter (PfCRT) mediates multidrug resistance, but its natural function remains unclear. Here, Shafik et al. show that PfCRT transports host-derived peptides of 4-11 residues but not other ions or metabolites, and that drug-resistance-conferring PfCRT mutants have reduced peptide transport.